Sharia Bank Marketing Management Concepts - Susila Andriyati; Muhammad Iqbal Fasa; suharto (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
The characteristics of products sold by banks are more services and not goods. Products sold are abstract or cannot be seen in absolute terms but can still be felt by customers. This research method is qualitative in the form of a literature review. Data in journals, books and encyclopedias related to the research focus. The data collection used is to look for literature that correlates or is in line with the main subject of the research. The marketing management concept asserts that the key to achieving organizational goals is that the company must be more effective than competitors in creating, delivering, and communicating customer value to its selected target markets. Kotler defines the marketing mix as a set of controllable factor marketing tools, products, prices, promotions, and places that the company integrates to produce the desired response in the target market. Saladin defines the marketing mix as a series of marketing variables that can be mastered by the company and used to achieve goals in the target market.